Caracterização e comportamento de acessos de alecrim-pimenta (Lippia sidoides Cham.) mantidos em banco ativo de germoplasma em São Cristóvão - SE - Oliveira, Tereza Cristina de (2008)
Pepper-rosmarin (Lippia sidoides Cham.) is a medicinal and aromatic plant, native Northeast Region of Brazil, which has an essential oil widely used for its properties as bactericide, fungicide, molluscicide, and larvicide. This paper aimed to characterize and evaluate the performance of accessions of pepper-rosmarin (Lippia sidoides Cham.) native to various States of the Northeast Region, kept in Germplasm Bank at São Cristóvão, Sergipe, Brazil. The first chapter presents the general introduction, the literature review on genetic resources and sustainability of agroecosystems, origin, ethnobotany, and germplasm characterization (morphological, agronomic and chemical). The second chapter presents and discusses the data on the morphological and agronomic characterization of accessions of pepper-rosmarin cultivated in field with seedlings from stem cuttings, using a randomized complete block design with two replications. The evaluated variables were: plant height, fresh and dry matter from leaves and stem, width and length of leaves, color of leaves and stem, crown shape, and content and yield of essential oil. Results showed morphological differences among accessions for color of stem, crown shape, plant height, width and length of leaves and ratio length/width of leaves. For agronomic variables, there were significant differences for content and yield of essential oil with the best and worst performance for accessions LSID-005 and LSID-105, respectively. Third chapter presents the data on performance evaluation of pepper-rosmarin, during two years of field cultivation, for the variables: plant height, fresh and dry matter of stem and leaves, content and yield of essential oil, and the content of chemical components of the essential oil. The higher averages found for content (7,68 %) and yield (56,46 mL plant- 1) essential oil were produced by the accession LSID-105, in 2005, and by LSID-102, in 2006, respectively. The higher averages for content of thymol (90,82 %) and carvacrol (56,05 %) were obtained from the accessions LSID-003 and LSID-104, respectively, both in 2006. The accession LSID-104, native to Sergipe State, presented carvacrol as major chemical component. All the other accessions presented thymol as major chemical component. All the accessions, in both years, presented phenotypical variability for all the evaluated variables, except for content of terpil-4-ol. Fourth chapter presents the evaluation of influence of dry and rainy seasons on the performance of accessions of pepper-rosmarin, using the variables: plant height, dry matter of leaves, content and yield of essential oil and content of chemical components of the essential oil. For the majority of the studied accessions, the thymol content was higher during the rainy season. LSID-102 accession presented high yield of essential oil (56,46 mL plant- 1) and thymol content between 47,97 % and 64,95 %. LSID-003 accession yielded 10,06 mL plant-1 of essential oil amd thymol content of 90,02 %. LSID-104 accession presented high content of carvacrol (54,68%) and low content of thymol (7,88 %). Fifth chapter presents the evaluation of the influence of leaves dehydration (at 40 °C for 5 days) on the content of essential oil and its chemical components of 11 accessions of pepper-rosmarin harvested during dry and rainy season. Generally, drying of leaves modified the content of most of the chemical constituents. In relation of the major iv chemical constituents, drying modified thymol content, but did not modified the carvacrol content of the essential oil of the pepper-rosmarin accessions.